2023
DOI: 10.1371/journal.pone.0284109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice of childhood apraxia of speech in Hong Kong: A web-based survey study

Abstract: Background A survey study on clinical practice not only provides insight into the implementation of knowledge, but also informs future investigations. There is a limited understanding of childhood apraxia of speech (CAS) in Cantonese speakers. This study examined the clinical practice of CAS in Hong Kong and discussed future directions of research for better evidence-based practice. Methods Qualified Hong Kong pediatric speech-language pathologists (SLPs) completed the online questionnaire, which had a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“… A pilot randomized control trial comparing ReST and ultrasound biofeedback treatment outcomes in children with CAS. 10 [ 67 ] The research aimed to examine the clinical practice of CAS in Hong Kong to inform future research and evidence-based practice. The study found that local SLPs’ understanding of CAS was limited and that evidence for the assessment, diagnosis, and treatment of Cantonese speakers with CAS was lacking.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… A pilot randomized control trial comparing ReST and ultrasound biofeedback treatment outcomes in children with CAS. 10 [ 67 ] The research aimed to examine the clinical practice of CAS in Hong Kong to inform future research and evidence-based practice. The study found that local SLPs’ understanding of CAS was limited and that evidence for the assessment, diagnosis, and treatment of Cantonese speakers with CAS was lacking.…”
Section: Resultsmentioning
confidence: 99%
“…Such collaboration underscores the need for a unified clinical language and fosters a holistic approach to addressing the multifarious challenges faced by children with CAS. Furthermore, the cultural and linguistic context within which CAS is assessed cannot be overstated, as it shapes both the interpretation of symptoms and the subsequent intervention strategies [ 59 , 67 ]. This is of particular salience in multilingual societies, where the nuances of different languages and cultural norms must be carefully negotiated to ensure equitable and effective diagnostic and therapeutic practices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations